Analysis of basidiomycete pigments in situ by Raman spectroscopy - Tauber, James P.; Matthaeus, Christian; Lenz, Claudius; Hoffmeister, Dirk; Popp, Juergen (Journal of Biophotonics, 2018)
Basidiomycetes, that is, mushroom-type fungi, are known to produce pigments in response to environmental impacts. As antioxidants with a high level of unsaturation, these compounds can neutralize highly oxidative species. In the event of close contact with other microbes, the enzymatically controlled pigment production is triggered and pigment secretion is generated at the interaction zone. The identification and analysis of these pigments is important to understand the defense mechanism of fungi, which is essential to counteract an uncontrolled spread of harmful species. Usually, a detailed analysis of the pigments is time consuming as it depends on laborious sample preparation and isolation procedures. Furthermore, the applied protocols often influence the chemical integrity of the compound of interest. A possibility to noninvasively investigate the pigmentation is Raman microspectroscopy. The methodology has the potential to analyze the chemical composition of the sample spatially resolved at the interaction zone. After the acquisition of a representative spectroscopic library, the pigment production by basidiomycetes was monitored for during response to different fungi and bacteria. The presented results describe a very efficient noninvasive way of pigment analysis which can be applied with minimal sample preparation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: basidiomycetes; multipartner interactions; natural products; pigments; Raman spectroscopy